Pengaruh Struktur Modal, Kepemilikan Manajerial dan Kinerja Keuangan Terhadap Nilai Perusahaan (Studi Pada Perusahaan Manufaktur yang Terdaftar di ISSI Tahun 2021-2023) - Putri Fitriana, Priska; Nur Azizah, Siti; Budi Santoso, Suryo; Pramono, Hadi (Journal of Accounting and Finance Management, 2025)
This study aims to examine the influence of Capital Structure, Managerial Ownership, and Financial Performance on Company Value. The object of the research conducted is manufacturing companies listed in the Sharia Stock Index in 2021-2023 which totals 130 companies. The theory used in this study is signal theory. Research data is quantitative secondary data obtained through the Indonesia Stock Exchange (www.idx.com). The sampling method carried out in the study was the purposive sampling technique, with the sample used amounting to 29 companies. The research data was analyzed using multiple linear regression using SPSS 26. The results of the study show that Capital Structure and Financial Performance have an effect on the company's value, while Managerial Ownership has no effect on the company's value.